Clinical information systems in the intensive care unit. Issue 1 (January 2016) - Mason, Christopher; Leong, Tim
Abstract: Clinical information systems (CIS) are used to collect, process, and present data for use in patient care. Common applications in the intensive care unit are charting, computerized physician order entry (CPOE), clinician decision support (CDS), and health information exchange. Benefits of CIS include increased efficiency, increased quality of care, and improved data availability, structure, and security. Possible risks include certain errors, reduced speed and efficiency, and loss of data security. Implementation of a CIS should follow a project management approach with a well-defined scope, involvement of clinicians, workflow analysis, and understanding of the limited life span of technical systems.